2013
DOI: 10.1080/01446193.2012.747689
|View full text |Cite
|
Sign up to set email alerts
|

UK construction site safety: discourses of enforcement and engagement

Abstract: Developments in safety management on large UK construction sites have seen a paradigm shift from enforcement-based systems to safety-culture programmes, which seek to engage with the workforce to create fully cooperative and safety-conscious sites. Founded in social constructionism, recent research sought out the master discourses of safety on large UK construction sites through the examination of safety signage, talk around safety and safety documentation. Two of the most prominent discourses of safety on sit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
53
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 55 publications
(58 citation statements)
references
References 23 publications
3
53
0
2
Order By: Relevance
“…This study builds on similar work previously carried out within the commercial construction sector by Sherratt et al (2012Sherratt et al ( , 2013. This work revealed the potential for a social constructionist approach to reveal safety in a meaningful and relevant way, through the discourses around safety found within large UK construction site environments.…”
Section: Methodssupporting
confidence: 64%
See 2 more Smart Citations
“…This study builds on similar work previously carried out within the commercial construction sector by Sherratt et al (2012Sherratt et al ( , 2013. This work revealed the potential for a social constructionist approach to reveal safety in a meaningful and relevant way, through the discourses around safety found within large UK construction site environments.…”
Section: Methodssupporting
confidence: 64%
“…Previous social constructionist work around safety has established some dominant discourses drawn upon by participants with regard to safety in their commercial construction work, including the associations of safety with practice, safety with Personal Protective Equipment (PPE) and safety invoked as a tool of enforcement or engagement (Sherratt et al 2012(Sherratt et al , 2013. Whilst these discourses also emerged during the analysis carried out for this study, alternative discourses were also drawn upon by the participants that were unique to their voluntary construct context.…”
Section: Methods Of Analysismentioning
confidence: 87%
See 1 more Smart Citation
“…Another study found that the social identity of a workgroup among construction workers influenced safety behaviour and safety rules implemented from site management (Andersen et al 2015). Finally, a study revealed several different discourses of safety depending on different organizational levels at a construction site (Sherratt et al 2013). These results underline variations in beliefs, attitudes, behaviour and social identity among sub-groups within the organization at construction sites, and that the lack of acknowledgement of such realities may be barriers for the success of safety programmes.…”
Section: Social Identity At Construction Sitesmentioning
confidence: 98%
“…This has led researchers and practitioners to focus on organizational and social factors such as social identity (Phua and Rowlinson 2004, Brown and Phua 2011, Sherratt et al 2013, Andersen et al 2015, and group-level safety climate (Zohar 2008 at the construction sites to induce positive safety change. However, previous research has examined safety climate and social identity at constructions sites separately.…”
Section: Introductionmentioning
confidence: 99%